PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI MODEL DISCOVERY LEARNING - Erni Ekafitria Bahar; Muhammad Rizal Usman; Indar Arum Pratiwi (JURNAL MathEdu (Mathematic Education Journal), 2022)
This study is a development research that aims to produce mathematical learning tools on comparative material through a discovery learning model in class VII students of MTs Muhammadiyah Wuring that are valid, practical, and effective. The development model employed in this study referred to 4D development model, which consisted of define, design, develop, and disseminate. The resulted product is in the form of RPP and LKPD with a discovery learning model on comparative material that can train students ability to solve problems and can make students easily understand mathematical concepts and improve their learning outcomes. The learning tools that had been developed was then validated by tho experts. After validated, the learning device was tested at 22 students of class VII MTs Muhammadiyah Wuring. The result of the study show that the learning tools in the form of RPP and LKPD of the discovery learning model that have been developed have been validated and show that the averages are 3,7 and 3,5 respectively, with very valid criteria. The learning tools based on discovery learning is stated as practical and effective, because the results of the practically test reveal: (1) The percentage of feasibility of the learning tools RPP and LKPD is 93,62% and 88,89% with a very decent category, and (2) The teacher’s ability in managing the discovery learning model of mathematics learning is very good with an average of 3,56. This learning tools also meets the criteria of effectiveness, with: (1) The student learning outcomes obtained an average score of 76,67 with completeness percentage is 81,8%, (2) The student activity shows a very good category with an average of 3,59, (3) the result of observations on the ability of teachers to manage mathematics learning using the discovery learning model show an average of 3,56 with a very good category, (4) The students gave a positive response to the learning tools with the discovery learning model with a percentage of 86%. Therefore, the results of the study shows that the product of learning tools developed is categorized as valid, practical, and effective.